Hyers-Ulam stability of a finite variable mixed type quadratic-additive functional equation in quasi-Banach spaces - K. Tamilvanan; Jung Rye Lee; Choonkil Park (AIMS Mathematics, 2020)
In this paper, we introduce a mixed type finite variable functional equation deriving from quadratic and additive functions and obtain the general solution of the functional equation and investigate the Hyers-Ulam stability for the functional equation in quasi-Banach spaces.